Transdisciplinary models of hydraulic drives of mobile machinery - A. V. Puzanov (Системный анализ и прикладная информатика)
Modern drive engineering requires a comprehensive analysis of all work processes in hydraulic drives, solving the problems of modeling the technological processes of their production using mathematical and software tools of various physicality.The article proposes an approach to the development of hydrodrives of mobile equipment based on transdisciplinary models of instruments and control systems. These models are designed to unite in a single information space a methodical and mathematical apparatus of various physicality: mechanics, kinematic, hydromechanics, heat engineering, and methods for their solution. These measures will increase their adequacy, reduce assumptions and reduce the safety factor as a measure of imperfection of the scientific and technical understanding of the facility.The article gives an example of the use of this approach in the development of volumetric hydraulic drives of mobile equipment a technique for calculating the indicator diagram of an axial-plunger hydraulic machine at a micro level using the Matlab / Simulink, Autodesk Simulation CFD and Autodesk Simulation Mechanical software complexes. The indicator diagram of the hydraulic machine is a clear characteristic of the dynamic qualities of the product. From the correctness of the calculation of this characteristic, the dynamic properties, reliability and resource of the drive as a whole depend.